Differences In Pulmonary TB Incidence In Highland And Coastal Areas In Barru District - Nuramalia Nuramalia; Fitriani Umar; Rini Anggraeny; Henni Kumaladewi Hengky; Haniarti Haniarti (Indonesian Journal of Health Science, 2026)
Pulmonary tuberculosis, caused by Mycobacterium tuberculosis, remains a global health issue. In Barru District, the number of pulmonary TB cases increased from 327 in 2023 to 464 in 2024. This study aims to investigate differences in the incidence of pulmonary TB between two locations: highland and coastal areas. The method used is quantitative analytical with a cross-sectional approach, involving 86 pulmonary TB patients from Lisu and Padongko Health Centers selected through simple random sampling. In the highlands, most patients were over 60 years old (43.5%), while in the coastal areas, the majority were aged 51â€“60 years (83.3%). Male patients were more numerous in both locations, with generally low educational levels. The most common occupations in the highlands were housewives and self-employed individuals, while in coastal areas, the majority were unemployed. No significant differences were found in age (Ï=0.494), gender (Ï=0.255), education (Ï=1.000), occupation (Ï=0.665), socioeconomic status (Ï=0.978), housing density (Ï=0.083), ventilation (Ï=0.083), or access to healthcare services. There were no significant differences in TB incidence. It is recommended that the elderly undergo regular health check-ups and maintain a healthy lifestyle to enhance their resistance to pulmonary TB infection.